Machining parameter selection in milling epoxy granite composites based on AHP. (2021) - Arun Ramnath, R.; Thyla, P.R.; Harishsharran, A.K.R.
Abstract: Machine tool structures fabricated with new alternate material epoxy granite has been developed to enhance the damping characteristics, stability and reduction in weight. Machining of epoxy granite composites (EGCs) has been critical by considering its heterogeneous nature. An optimization problem with multiple attributes has become a critical issue in selection of optimal solution due to the varying characteristics among attributes. Decision making model, Analytical hierarchy procedure (AHP) is employed in selection of optimal machining condition in milling EGCs. Evaluation factors consisting attributes that influences machining process such as thrust force, tangential force and surface roughness are only considered. Computation from AHP method reveals that experimental run 3 is the desired optimal solution with the optimal machining conditions of speed 600 rpm; feed rate 0.09 m/min and 4% fiber content.